Communism and anti-Communism in early Cold War Italy : language, symbols and myths - Mariuzzo, Andrea, 1979- (Manchester University Press, 2018)
The books detects the struggle of Communism and anti-Communism as a key feature for the making of the political system in post-WWII democratic Italy, and presents it in its international context through a broad analysis of the main communication networks.